2019
DOI: 10.3390/cells8020101
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Corticotropin-Releasing Factor Receptors and B7-2+ Extracellular Vesicles in Blood Correlate with Irritable Bowel Syndrome Disease Severity

Abstract: Extracellular vesicles (EVs) are composed of bilayer membranes that are released by different cell types and are present in bodily fluids, such as blood, urine, and bile. EVs are thought to play a key role in intracellular communication. Based on their size and density, EVs are classified into small, medium, or large EVs. Cargo composition in EVs reflects physiological changes in health and disease. Patients with irritable bowel syndrome (IBS) exhibit visceral hypersensitivity and mood disorders. Stressful epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The higher molecular weight observed in this receptor could be due to glycosylation or related-mechanism likely to facilitate their transport in blood serum. In accordance, circulating CRF receptor I/II were also detected at a discrete but higher molecular weight in human blood serum [32]. Regarding mGluR 5 , it was found a band at 125-130 kDa, which is in line with the predicted weight estimated by the manufacturer's indications, suggesting that this receptor might be released as a full-length molecule.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The higher molecular weight observed in this receptor could be due to glycosylation or related-mechanism likely to facilitate their transport in blood serum. In accordance, circulating CRF receptor I/II were also detected at a discrete but higher molecular weight in human blood serum [32]. Regarding mGluR 5 , it was found a band at 125-130 kDa, which is in line with the predicted weight estimated by the manufacturer's indications, suggesting that this receptor might be released as a full-length molecule.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of different GPCRs in blood serum has been evidenced before. Corticotropin releasing-factor receptors I/II (CRF receptor I/II) were reported as circulating receptors in extracellular vesicles (EVs) from blood serum [32]. Additionally, the purinergic receptor P2 × 7 was found as EVs cargo in human blood serum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular vesicles-mediated cell-cell communication impacts physiological changes in health and disease. For example, vesicles secreted from immune cells change adaptive and innate immune responses via exchange of vesicles between different immune cell types in patients with irritable bowel syndrome (Hagiwara et al 2019). This study indicated that the vesicle contents are relatively specific on basis of cell phenotype and function.…”
Section: Roles Of Extracellular Vesiclesmentioning
confidence: 72%